Integration of environmental impact assessment and environmental management systems in shell’s EIA rectification process in the Gauteng Province in South Africa - Chaka, I.; Jerie, Steven (Midlands State University, 2015)
There are tensions between the state and business in the regulation of environmental matters. Some problems experienced in the application of Environmental Impact Assessment (EIA) in South Africa between the state administered environmental legislation and a corporate representative of the business world are exemplified in Shell’s EIA Rectification Process for fuel storage tanks in the Gauteng Province, South Africa. This paper highlights some of these problems and, in response, proposes the implementation of an Environmental Management System (EMS) as a tool for the ongoing management of the fuel storage tanks after the rectification process. Practical and theoretical perspectives of both EIAs and EMSs are discussed, and an EMS based on the South African National Standard (SANS) ISO 14001 framework is proposed to manage the tanks. A brief background of the Rectification Process is given, putting into perspective the need for a comprehensive system for improved tank management.